Recurso educativo digital gamificado Secuencias numéricas como generador de aprendizajes y motivación en la asignatura de Matemáticas del tercer grado de educación general básica en la Unidad Educativa Fiscomisional La Dolorosa de la ciudad de Loja, año lectivo 2022 – 2023. - Coronel Quizhpe, Jefferson Humberto (2023)
The teacher, by using basic didactic material found in the classroom, such as notebooks, the guide book, the blackboard and the occasional sheet, loses the opportunity to stimulate the training process mediated by the use of technologies, therefore, This curricular integration work is a contribution to the knowledge of how the gamified digital educational resource Secuencias numéricas contributes and behaves during the execution of a class, so that it is capable of generating learning and motivation. The research was carried out using the inductive-deductive study method, with a qualitative and quantitative approach, the scope of the research is descriptive exploratory and a non-experimental type of design, the same one that focused on analyzing the gamified digital educational resource Secuencias Numéricas as a generator of learning and motivation in the subject of mathematics of the third grade of basic general education in the Fiscomisional Educational Unit “La Dolorosa”, for data collection three instruments were built based on the criteria to measure the quality of digital educational materials of the “Instituto Nacional de Tecnologías Educativas y de Formación del Profesorado”, the first of these is an observation sheet, taking into account the didactic moments of a class, the second and third are: a structured questionnaire and an evaluation sheet, both instruments are adapted from Annex F (Informative) of the norm of the “Asociación Española de Normalización”. These instruments were applied to the sample of this investigation that are: 1 teacher and 25 students, thus allowing to obtain the results and reactions in face-to-face classes. Observing the didactic moments, it is confirmed that the didactic digital material used during three class sessions generates learning and motivation. Keywords: Digital educational resource, Gamification, Learning and motivation, Didactic moments.